PENGARUH KOMPETENSI GURU EKONOMI TERHADAP PRESTASI BELAJAR SISWA KELAS XI-IPS DI SMA KRISTEN PETRA 3 SURABAYA - PUSPITA ANDRIANTO, RIA (Universitas Negeri Surabaya, 2016)
ABSTRACT Competence of teacher is an important factor to note in order to improve the quality of education, made possible factors can influence learning achievement that the study aims to determine the influence of the economic competence of teachers to learning achievement students. This study used 73 samples from two classes IPS.Analysis of data using a simple liniear regression technique with the aid of a computer program SPSS 18.00for windows that is known to have a significant influence and classified as very strong between teacher competence (x) with learning achievement students (y) in equal to 0.000. furthermore, to determine the strength of the effect of independent variables and the dependents variables simultaneously, we used a simple liniear regression formula, so the effect is known to have a realitively strong correlation between the variable x and y for 0,482. Of the velue of coefficient of determination is known to have the effect of 48,2% between the independent variables and the dependents variables and the 52,8% coused by other variables. And from the result of the test calculations show that F count Fcount > Ftable (0,707 > 0,312), which means that the influence of the independent variables and the dependents variable convince (significant). Conclusions from this study that the effect of the economic competence of teacher to learning achievement of students in class XI-IPS SMA Kristen Petra 3 Key words: Teacher competenc, Learning Achievement